Defects in muscle branched-chain amino acid oxidation contribute to impaired lipid metabolism - Carles Lerin; Allison B. Goldfine; Tanner Boes; Manway Liu; Simon Kasif; Jonathan M. Dreyfuss; Ana Luisa De Sousa-Coelho; Grace Daher; Irini Manoli; Justin R. Sysol; Elvira Isganaitis; Niels Jessen; et al. (Elsevier, 2016)
Objective: Plasma levels of branched-chain amino acids (BCAA) are consistently elevated in obesity and type 2 diabetes (T2D) and can also prospectively predict T2D. However, the role of BCAA in the pathogenesis of insulin resistance and T2D remains unclear. Methods: To identify pathways related to insulin resistance, we performed comprehensive gene expression and metabolomics analyses in skeletal muscle from 41 humans with normal glucose tolerance and 11 with T2D across a range of insulin sensitivity (SI, 0.49 to 14.28). We studied both cultured cells and mice heterozygous for the BCAA enzyme methylmalonyl-CoA mutase (Mut) and assessed the effects of altered BCAA flux on lipid and glucose homeostasis. Results: Our data demonstrate perturbed BCAA metabolism and fatty acid oxidation in muscle from insulin resistant humans. Experimental alterations in BCAA flux in cultured cells similarly modulate fatty acid oxidation. Mut heterozygosity in mice alters muscle lipid metabolism in vivo, resulting in increased muscle triglyceride accumulation, increased plasma glucose, hyperinsulinemia, and increased body weight after high-fat feeding. Conclusions: Our data indicate that impaired muscle BCAA catabolism may contribute to the development of insulin resistance by perturbing both amino acid and fatty acid metabolism and suggest that targeting BCAA metabolism may hold promise for prevention or treatment of T2D. Keywords: Insulin sensitivity, BCAA, Fatty acid oxidation, TCA cycle